Leading AI-Driven Student Engagement: The Role of Digital Leadership in Higher Education - Melita Kovacevic; Tamara Dagen; Miroslav Rajter (Education Sciences, 2025)
This theoretical position paper explores the potential of artificial intelligence (AI) to enhance student engagement through the lens of academic leadership. To illustrate our argument, we include exploratory, mixed-methods evidence drawn from a descriptive survey of 95 undergraduate students and five semi-structured interviews with key academic leaders. These data are indicative only and not intended for statistical generalisation; however, they ground and inform the theoretical propositions of this paper. Focusing on how AI-driven tools can be used, the study examines the central role of academic leaders in guiding these innovations. By addressing key leadership decisions—including resource allocation, policy development, and faculty support—the study explores how AI can foster a more responsive and engaging learning environment and provides insights into how academic leadership can guide the integration of AI technologies to increase student motivation, participation and academic success in different educational settings.